Post-harvest practices for aflatoxin control: Evidence from Kenya - Pretari, Alexia; Hoffmann, Vivian; Tian, Lulu (Elsevier, 2019)
We assess the impact of a package of post-harvest technologies on aflatoxin contamination of maize through a randomized trial in rural Kenya. Some elements of this package (training and provision of plastic sheets for sun-drying) were provided free of charge to all participants in treatment villages and were widely adopted. Others (a mobile drying service and hermetic storage bags) were provided free to a subset of randomly selected farmers in treatment villages while others had to pay. Overall, the intervention reduced aflatoxin contamination by over 50%. Most of this reduction appears to be due training and the use of drying sheets, the lowest-cost of all the technologies offered.